2018
DOI: 10.1039/c8fo01407h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the intake of white wheat bread added with garlic and resistant starch: action on calcium bioavailability and metabolic parameters of growing Wistar rats

Abstract: Functional bread with resistant starch and garlic improved the metabolism of calcium and lipids and the growth of beneficial gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Instead, RS +G bread presents a slightly higher protein content and a much higher total dietary fiber content than wheat bread. This increase of the fiber content is of relevance since in vivo studies the use of RS with garlic (inulin source) has shown a prebiotic effect in Wistar rats contributing to the growth to the beneficial flora, improving the lipoprotein profile, and helping to a better bone health (Weisstaub et al., 2018). Therefore, bread made with functional ingredients presented a higher protein and dietary fiber content than wheat bread, providing a lower caloric value (192 kcal/100 g of bread versus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, RS +G bread presents a slightly higher protein content and a much higher total dietary fiber content than wheat bread. This increase of the fiber content is of relevance since in vivo studies the use of RS with garlic (inulin source) has shown a prebiotic effect in Wistar rats contributing to the growth to the beneficial flora, improving the lipoprotein profile, and helping to a better bone health (Weisstaub et al., 2018). Therefore, bread made with functional ingredients presented a higher protein and dietary fiber content than wheat bread, providing a lower caloric value (192 kcal/100 g of bread versus.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Weisstaub et al. (2018) studied the effects of bread with garlic and resistant starch (RS +G) as fiber source on physiological, metabolic, and functional parameters using an in vivo Wistar rat model. This study showed that animals fed with this bread formulation increased the lactobacilli/enterobacteriaceae ratio, which correlated with a lower cecal pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results might be related to SCFAs by the intestinal microbial fermentation of RS. In addition, it was reported that bread with RS4 and garlic showed a prebiotic effect and increased Ca bioavailability and deposition in bones in male weaning Wistar rats, compared with wheat bread (Weisstaub et al 2018). However, Schulz et al (1993) found that apparent absorption of Ca and Mg in rats was improved by RS2 (uncooked highamylose starch granules) but not by RS3 (cooked and cooled high-amylose starch).…”
Section: Improving Mineral Absorption In Large Intestinementioning
confidence: 99%
“…25 From the previous studies, RS played a useful role in health by some potential mechanisms include: ① changes in intestinal microbiota, ② a reduction in insulin, ③ resistance rise in HDL-c concentrations, and ④ an increase in SCFAs production. [3][4][5][6][26][27][28][29][30][31][32][33][34] RS could produce SCFAs through two pathways: directly (RS fermentation) or indirectly (increasing colonic butyrate-producing microbiota such as Lachnospiraceae and Ruminococcaceae). Butyrate can control macrophage activity and expression of NF-κB which is the main inflammatory and immune response.…”
Section: Summary Of Evidencementioning
confidence: 99%